Structural Reliability Analysis of Wind Turbines: A Review - Zhiyu Jiang; Weifei Hu; Wenbin Dong; Zhen Gao; Zhengru Ren (Energies, 2017)
The paper presents a detailed review of the state-of-the-art research activities on structural reliability analysis of wind turbines between the 1990s and 2017. We describe the reliability methods including the first- and second-order reliability methods and the simulation reliability methods and show the procedure for and application areas of structural reliability analysis of wind turbines. Further, we critically review the various structural reliability studies on rotor blades, bottom-fixed support structures, floating systems and mechanical and electrical components. Finally, future applications of structural reliability methods to wind turbine designs are discussed.